2020
DOI: 10.1108/aaouj-11-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning source of satisfaction of psychological needs

Abstract: PurposeIn this study, researchers applied blended learning program to investigate the success of a blended learning program on satisfaction of the psychological needs, and academic achievement of chemistry students of O-Levels, following curriculum prescribed by University of Cambridge.Design/methodology/approachResearch pattern is quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…The application of learner-centered method in blended learning is a good combination to enhance the participants' competencies. This concept is similar to the findings of Siddiqui et al (2020) that blended learning somehow has substantial association with other psychological needs such as being more competent and more relatable. Hence, the adoption of blended learning provided the participants the varied learning spaces.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The application of learner-centered method in blended learning is a good combination to enhance the participants' competencies. This concept is similar to the findings of Siddiqui et al (2020) that blended learning somehow has substantial association with other psychological needs such as being more competent and more relatable. Hence, the adoption of blended learning provided the participants the varied learning spaces.…”
Section: Resultssupporting
confidence: 87%
“…Thus, the new educational set-up called blended learning existed in most educational institutions. Blended learning, also known as hybrid learning, is an educational approach utilizing both online educational materials and opportunities for interaction online with traditional place-based classroom methods (Yeap et al, 2022;Siddiqui et al, 2020;Quigley, 2019;). This means that both teachers and learners are in a compromising stage in the new academic landscape with a common goal of continuous teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of self-determination emphasizes the tendency of individuals to bring up a series of behavioral effectiveness that is oriented towards the achievement of learning outcomes (Siddiqui, Soomro & Thomas, 2019). The focus of the study of self-determination theory is based on intrinsic motivation and internalization processes that are oriented towards individual attitudes and goals in generating behavior that is focused on learning outcomes (Abeysekeraa & Dawson, 2015).…”
Section: Self-determination's Role In Students Academic Performancementioning
confidence: 99%
“…Asian students show the tendency to recognize the teacher's role in assessing their learning above their own. Siddiqui et al (2019) [42] argued that teachers is one important participant in a successful learning. Teacher could provide a supporting learning environment to improve students positive and autonomous.…”
Section: Discussionmentioning
confidence: 99%
“…Siddiqui et al (2020) [8] studied the psychological needs of students in blended learning and found that blended learning could help enhance the learning outcomes when it provides an autonomous rather than controlled environment. In a variety of subject areas, including language learning, information technology and engineering, blended learning has also been shown to enhance learning through collaborative and self-paced learning approaches (K. K. & Maskari, 2019) [9] .…”
Section: Introductionmentioning
confidence: 99%